Statutory elements of the crime of motor vehicle registration plates forgery - Stefańska, Blanka Julita (Ius Novum, 2024)
This article is of a scientific and research nature and covers the subject of offences defined in Article 306c of the Criminal Code, which has been in force since 1 October 2023. It addresses, inter alia, the counterfeiting or altering of a motor vehicle registration plate to use it as an authentic one (§ 1) and using it as an authentic one (§ 2). The primary research goal is to assess the reasonableness of introducing this provision into the Criminal Code and the correctness of determining the conditions for its application and its objective scope. The assumption is that the criminalisation of such behaviour could be an effective weapon in combating the phenomenon of fuel theft from petrol stations, as the perpetrators of these thefts usually attach counterfeit plates to their vehicles. The analysis covers the object of protection of this provision, the types of this crime, their elements such as counterfeiting and alteration, the concept of a registration plate, the legalisation of the plate, the purpose of the causative behaviour, and the concept of a motor vehicle. It is sufficient to use the normative and dogmatic method to analyse the issues.